Improved yield of canine islet isolation from deceased donors - Harrington, Stephen (BMC Vet Res, 2017)
BACKGROUND: Canine diabetes is a strikingly prevalent and growing disease, and yet the standard treatment of a twice-daily insulin injection is both cumbersome to pet owners and only moderately effective. Islet transplantation has been performed with repeated success in canine research models, but has unfortunately not been made available to companion animals. Standard protocols for islet isolation, developed primarily for human islet transplantation, include beating-heart organ donation, vascular perfusion of preservation solutions, specialized equipment. Unfortunately, these processes are prohibitively complex and expensive for veterinary use. The aim of the study was to develop a simplified approach for isolating canine islets that is compatible with the financial and logistical restrictions inherent to veterinary medicine for the purpose of translating islet transplantation to a clinical treatment for canine diabetes. RESULTS: Here, we describe simplified strategies for isolating quality islets from deceased canine donors without vascular preservation and with up to 90 min of cold ischemia time. An average of more than 1500 islet equivalents per kg of donor bodyweight was obtained with a purity of 70% (N = 6 animals). Islets were 95% viable and responsive to glucose stimulation for a week. We found that processing only the body and tail of the pancreas increased isolation efficiency without sacrificing islet total yield. Islet yield per gram of tissue increased from 773 to 1868 islet equivalents when the head of the pancreas was discarded (N = 3/group). CONCLUSIONS: In summary, this study resulted in the development of an efficient and readily accessible method for obtaining viable and functional canine islets from deceased donors. These strategies provide an ethical means for obtaining donor islets.